The Gambia : Addendum to the Joint Staff Advisory Note on the Second Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
The Gambian authorities produced two Annual Progress Reports (APRs) covering implementation of the first Poverty Reduction Strategy Paper (PRSP) during 2002-03 and 2004, respectively. This addendum is organized around four of the main themes of the first PRSP: (i) macroeconomic stability and effective public resource management; (ii) promotion of pro-poor growth and employment creation through private sector development, particularly in the rural agricultural sector; (iii) improved basic social services and infrastructure; and (iv) capacity-building of local communities and civil society organizations (CSOs).